Streamlined stationary phase selection facilitated by a "sample-plug retention test" in supercritical fluid extraction-supercritical fluid chromatography-mass spectroscopy (SFE-SFC-MS) method development for on-line extraction of anabolic agents. Issue 17 (14th December 2021) - Berger, Blair K.; Wicker, A. Paige; Preuss, Emily K.; Fujito, Yuka; Hedgepeth, William; Nishimura, Masayuki; Schug, Kevin A.
Abstract: A novel method development (MD) approach was established to aid column selection for online supercritical fluid extraction-supercritical fluid chromatography-mass spectrometry (SFE-SFC-MS). An adapted stationary phase (SP) selection procedure was used to expand traditional SFC-MS screening by inclusion of an "Analyte-Plug Retention Test." This test enabled an early evaluation of "trapping" capability for a plug of targeted analytes on the SP. Using an SFE-simulation method, the on-line trapping of an SFE-based extract-plug was mimicked by trapping an SFC-based injection-plug under instrument conditions similar to an actual on-line extraction. Thirteen SPs were screened using the adapted MD procedure as part of the SFC-separation optimization in the development of an on-line SFE-SFC-MS extraction method for anabolic agents (AAS) in anti-doping testing. A cyano SP was chosen for further development, based on chromatographic separation potential and high plug-retention potential for targeted analytes. The chosen column was used in "proof-of-concept" on-line extractions using a generic SFE-SFC-MS method. Successful extract-plug trapping was demonstrated. Retention times and peak areas (4–20%RSD) were reproducible for targeted AAS. Successful first round SFE-SFC-MS SP selection was demonstrated to circumvent tedious re-optimization in future development stages and streamlining of the hyphenated SFE-SFC-MS MD process. Graphical Abstract: UF0001